Italy : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
The Selected Issues paper investigates options for improving the efficiency of the Italian judicial system and closing the regional performance gap. Better courts would bring about macroeconomic benefits, including increased employment opportunities, and higher productivity, investment, and research and development. The Italian financial system faces several challenges in order to restore profitability under weak growth conditions and to adapt to a changing global environment. This chapter explores ways of improving profitability and the challenges of shifting from a bank-based financial system, common in EU countries, to a more 'market-based' system. Along with this shift comes a diversification of financing sources, led by further development of capital markets. Budget allocation in Italy will need to increasingly rely on efficiency analysis to find savings and improve performance. The analysis in this chapter finds that large social spending in Italy, particularly current pensions, will need to be tackled to generate sizable expenditure savings. In education and non-pension social protection there is scope for improving outcomes with current resources. In other areas, reducing cross-regional variation in spending efficiency could also lead to savings. Reforms should focus on court management, rationalization of the appeal system, reduction of the backlog of pending cases, and wider use of out-of-court mediation.